LASER TECHNIQUES IN THE STUDY OF MATERIALS. (Universal International Scientific Journal, 2026)
This article discusses the theoretical foundations and practical application areas of lasertechniques in the study of materials. The role of laser techniques in materials science, chemistry,biology, ecology, and nanotechnology is also highlighted. It is emphasized that laser-based methods aredistinguished by high sensitivity, rapid analysis, and the ability to perform non-contact measurements.
Keywords: aser radiation; spectroscopy; Raman effect